2023
DOI: 10.3390/pr11030718
|View full text |Cite
|
Sign up to set email alerts
|

Hemp: An Alternative Source for Various Industries and an Emerging Tool for Functional Food and Pharmaceutical Sectors

Abstract: Hemp is a high-value crop that originated in Central Asia and is a historic but emerging cultivated plant. It may be grown for fiber, food, paper making, textiles, and therapeutic reasons. In the 21st century, market interest in hemp and its products has notably increased because seed portions can be utilized in the agri-food business, the woody component of the stem can be used in green buildings, the outer layer of the stems can be used in the textile industry, and the extraction of bioactive components from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Although growth-promoter supplements have been used in animal diets for decades to improve health, they have been shown to have some adverse effects on meat quality that compromise human health (Kocher 2005). As a result, hemp is being employed as an alternative to the present growth promoters, some synthetic medicines and protein ingredients due to its superior nutritional attributes and medicinal benefits (Naeem et al 2023). Few studies have shown the medicinal properties of hemp to be responsible for the alleviation of stress (Wheeler and Fields 1993), enhance immunity (Zhu et al 1997) and suppress tumorous cells in animal bodies (Blázquez et al 2003).…”
Section: Effect Of Hemp On the Health Performance Of Farm Animalsmentioning
confidence: 99%
“…Although growth-promoter supplements have been used in animal diets for decades to improve health, they have been shown to have some adverse effects on meat quality that compromise human health (Kocher 2005). As a result, hemp is being employed as an alternative to the present growth promoters, some synthetic medicines and protein ingredients due to its superior nutritional attributes and medicinal benefits (Naeem et al 2023). Few studies have shown the medicinal properties of hemp to be responsible for the alleviation of stress (Wheeler and Fields 1993), enhance immunity (Zhu et al 1997) and suppress tumorous cells in animal bodies (Blázquez et al 2003).…”
Section: Effect Of Hemp On the Health Performance Of Farm Animalsmentioning
confidence: 99%
“…These supplements can be beneficial for anticonvulsant and anxiolytic effects. Hemp seed is an important supplement which contains amino acids, vitamins, minerals, fatty acids, fibres, etc [44], [45]. Consequently, hempseed oil contains healthy polyunsaturated fatty acids.…”
Section: Hemp Fibresmentioning
confidence: 99%
“…It can be grown in barren lands [25]. Hemp has long been used as a feedstock in the textile industry, as is widely known [26]. Additionally, it was also noted that hemp has a wide range of uses, including the construction industry, automotive, plastics, high-quality absorbents, paper, agriculture, personal cleaning, and healthcare.…”
Section: Introductionmentioning
confidence: 99%